Acute stress disorder in patients with traumatic spinal cord injury: risk factors and coping strategies - Shi, Haohua; Su, Yufang; Pan, Chunyan (Frontiers in Psychiatry, 2025)
BackgroundTraumatic Spinal Cord Injury (TSCI) exerts a profound negative impact on patients’ psychological well-being and daily life. The objective of this study is to dissect the comorbidity of Acute Stress Disorder (ASD) among TSCI patients, identify its contributing factors, and construct a predictive model to provide empirical support for clinical treatment and nursing care.MethodsPatients with TSCI admitted to our hospital between January 2022 and September 2024 were enrolled in this study. We collected and compared general demographic and disease-related data between patients who developed ASD and those who did not.ResultsA cohort of 224 individuals with TSCI was enrolled in the study, revealing an incidence rate of ASD to be 33.93%. Age (r=0.562), gender (r=0.489), monthly household income (r=0.585), and injury severity (r=0.722) were correlated with ASD. Age ≤45 years (OR=2.606, 95%CI: 1.985-3.215), female gender (OR=2.213, 95%CI: 2.004-2.612), monthly household income less than 5000 Renminbi (RMB) (OR=3.027, 95%CI: 2.677-3.431), and level A injury severity (OR=3.673, 95%CI: 3.115-4.066) were the independent predictors of ASD among patients with TSCI. The area under the ROC curve (AUC) and its 95% confidence interval (CI) were 0.788 (0.710, 0.852) for the predication model, indicating good sensitivity and specificity.ConclusionASD is a common occurrence in patients with TSCI, with a multitude of contributing factors. The predictive model established in this study aids in the risk assessment of ASD in patients with TSCI.